"Black Like Me": Reframing Blackness for Decolonial Politics. Issue 2 (4th March 2018) - Dei, George J. Sefa
Abstract : From a particular vantage point, as an African-born scholar with a politics to affirm my Black subjectivity and Indigeneity in a diasporic context, my article engages a (re)theorization of Blackness for decolonial politics. Building on existing works of how Black scholars, themselves, have theorized Blackness, and recognizing the fluid, intersecting, and contested nature of this concept, I engage a multidimensional reading of Blackness, in part as a counter to the insidious attempts to delegitimize Black radical/racial politics. The article grounds particular struggles at the curious interface of skin, body, psyche, hegemonies, and politics. The article, in particular, responds to the perceived tensions between race, Blackness, and Indigeneity, offering a way of rereading Blackness differently: (a) to include Africa(ness), as a strategic reinvention of Africanness in diasporic contexts; (b) to reclaim an African Indigeneity in global knowledge production as a way of knowing that speaks to histories, cultures, identities, African spiritual ontologies, and a politics of the African/Black body; (c) to undertake a conscious intellectual shift in reading Black/African diasporic presence on Indigenous peoples Lands from a discursive prism of "colonial settlerhood" and discourses of "complicities in our claims of citizenship" to one of "collective implications" and "differential responsibilities" so as to foster decolonization and, particularly, decolonial solidarities among colonized, oppressed, and Indigenous peoples; (d) to highlight questions of the responsibilities of the Black/African learner in the (Western) academy; and (e) to reread Black(ness) in ways that speaks to the continental African subject who may decry the color descriptor of Black(ness).